Cryptographic secrecy of steganographic matrix encoding - Jia-yong CHEN; Jiu-fen LIU; Yue-fei ZHU; Wei-ming ZHANG (Tongxin xuebao)
Based on an information theory model,the cryptographic security of matrix encoding,which can be applied in steganographic codes or wet paper codes,under different attack conditions was studied.The cryptographic security about matrix encoding under the condition of known-cover attack with key equivocation,message equivocation and unicity distance of stego-key was presented.The result that n groups of differential equations could sufficiently recover the share key of matrix encoding under the condition of chosen-stego attack was pointed out.